Analisis Perlakuan Akuntansi Syariah Pada Pembiayaan Murabahah Berdasarkan PSAK 102 Di Bmt Nu Cabang Banyuputih Kabupaten Situbondo - Andriyono Andriyono; Dhafir Miftah (Program Studi Akuntansi Syari'ah Universitas Ibrahimy, 2024)
The accounting treatment for murabahah financing in practice in BMT NU Banyuputih Branch, Situbondo Regency needs to be considered, as the accounting treatment must be in accordance with the accounting standards in PSAK 102 which includes a process to identify, measure, and report economic information that may have an assessment in making decisions that precise, clear and believable to its users and readers. Until now, many murabahah accounting treatments have not complied with the rules stipulated in PSAK no. 102. This study aims to determine the implementation of murabahah financing at BMT NU Banyuputih Branch, Situbondo Regency, as well as the rules for murabahah financing, murabahah financing procedures, and accounting for murabahah financing and suitability implementation with the Statement of Financial Accounting Standards PSAK no 102.This study aims to determine murabahah financing at BMT NU Banyuputih Branch, Situbondo Regency and the policies that have been applied in murabahah financing at BMT NU Banyuputih Branch, Situbondo Regency. The type of research in this thesis is descriptive qualitative research using field research methods. This study analyzed data obtained by researchers from interviews with BMT NU informants, Banyuputih Branch, Situbondo Regency.The results of this study indicate that the accounting treatment of murabahah at BMT NU Banyuputih Situbondo Branch regarding the recognition and measurement of the acquisition of assets is not recognized as a murabahah asset. Receivables are recognized at the agreed cost and profit. In murabahah profits are recognized in accordance with the customer's installments every month according to a mutually agreed period. And advances are recognized as a reduction in murabahah receivables. In presentation and disclosure, it is presented at the realized net value, while the murabaha margin is used as a deduction for murabahah receivables and disclosures on all matters related to murabahah financing. The accounting treatment for murabahah financing at BMT NU Banyuputih Situbondo Branch is in accordance with PSAK 102, namely both recognition and measurement, presentation and disclosure are almost in accordance with PSAK 102, only for advances and acquisition of assets that are not appropriate.